Interleukin-13 Increases Podocyte Apoptosis in Cultured Human Podocytes - Keum Hwa Lee; Ji Young Oh; Su-Bin Seong; Tae-Sun Ha; Jae Il Shin (Korean Society of Pediatric Nephrology, 2018)
Purpose Podocytes are important architectures that maintain the crucial roles of glomerular filtration barrier functions. Despite this structural importance, however, the mechanisms of the changes in podocytes that can be an important pathogenesis of minimal change nephrotic syndrome (MCNS) are not clear yet. The aim of this study was to investigate whether apoptosis is induced by interleukin (IL)-13 in cultured human podocytes. Methods Human podocytes were treated with different IL-13 doses and apoptotic cells were analyzed using terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL assay) and fluorescence-activated cell sorting (FACS). Results The IL-13 increased the number of TUNEL-positive cells in a dose-dependent manner at 6 and 18 hours (P <0.05 and P <0.05, respectively). The apoptosis rate was appeared to be increased slightly in the IL-13-stimulated podocytes (8.63%, 13.02%, and 14.46%; 3, 10 and 30 ng/mL, respectively) than in the control cells (7.66%) at 12 hours by FACS assay. Conclusion Our study revealed that IL-13 expression may increase podocyte apoptosis. Blocking the IL-13 signal pathway can potentially play an important role in regulating the apoptosis of podocytes.